(untitled) (Orfeu, 2018)
Human vocalization contains key essences of our musical development and fosters our earliest abilities to communicate musically. Speech melodies are the first linguistic elements experienced and mastered, and are indistinguishable from the melodic precursors of singing as essential elements in intraand inter-personal musical communication. Singing as communication originates in vocal pitch contours whose musical intervals are exploited by caregivers in infant-directed speech to foster language development. Similar, but more explicit, features are evidenced in caregivers’ infant-directed singing, such as in lullabies and play songs. These basic musical elements of communication can be perceived in utero and underpin the infant’s subsequent vocalizations and musical behaviors. Additionally, the underlying integration of emotion with perception and cognition generates a network of linked vocal and emotional behaviors that are central to human communication. The chapter will examine the growing evidence for musical communication as integral to human vocalization and emotional expression.